Implementation of the Tongke-Tongke Mangrove Forest Tourism Development Policy Implementation - Salman Salman; Juanda Nawawi; A. M. Rusli (Universitas Negeri Makassar, 2021)
Implementation of the policies of the Tourism and Culture Office of Sinjai Regency in the development of the Tongke-Tongke Mangrove Forest, several policies are less effective and efficient so that the Tongke-Tongke Mangrove Forest, especially infrastructure. Based on data from the tourism office in the RIPPARKAB of Sinjai Regency, the development of the Tongke-Tongke mangrove debt has been included in the list of tourism development objects in Sinjai Regency. The main formulation of this research is how to implement the Tongke-Tongke Mangrove Debt development program carried out by the tourism office. This research is qualitative descriptive research, this research was conducted through observation, interviews, in-depth, and documentation. And the data analysis technique is done by describing and describing and grouping the data according to the type of data. The results of this study indicate that what has been done by the Tourism Office of Sinjai Regency in optimal tourism development has been carried out according to what has been planned in the RPJMD of the tourism office. In the implementation of tourism development policies, of course, there are still obstacles or obstacles in implementing policies, such as in the recruitment of human resources not by the desired competencies, the lack of budget allocated in the development of Tongke-tongke mangrove forest tourism.